Co-occurring Chronic Conditions and Economic Burden among Stroke Survivors in the United States: A Propensity Score-Matched Analysis - Chanadda Chinthammit (2018)
© 2017 National Stroke Association Objective This study examined the impact of co-occurring chronic conditions on healthcare expenditures among noninstitutionalized older adults (age ≥50 years) with stroke in comparison to non–stroke-matched controls. Methods This study used a retrospective, cross-sectional, matched case-control design using pooled 2002-2012 Medical Expenditure Panel Survey (MEPS) data. Stroke survivors (N = 2913) were compared with matched controls (N = 8739) based on propensity scores. Healthcare expenditures for co-occurring chronic conditions were compared between stroke survivors and matched controls using ordinary least squares (OLS) regressions. All analyses were conducted in SAS 9.4 (SAS Institute Inc., Cary, NC, USA) using survey procedures adjusting for the complex survey design of the MEPS. Results The annual mean total healthcare expenditures (expressed in 2012 United States dollars) were significantly higher among stroke survivors compared with matched non-stroke controls ($18,796 versus $14,391, P < .001). OLS regressions revealed that co-occurring chronic conditions partially explained the excess healthcare expenditures among stroke survivors. The annual mean total healthcare expenditures among stroke survivors were significantly higher for most of the co-occurring chronic conditions compared with matched controls (e.g., in presence of hyperlipidemia, stroke survivor expenditures were $18,807 compared to $15,807 among matched controls). Stroke survivors with co-occurring arthritis, diabetes, or hypertension had significantly greater inpatient, emergency room, and prescription expenditures compared with matched controls. Conclusions Stroke survivors experience a high economic burden. Interdisciplinary team-based treatment approaches to provide holistic care may help reduce the burden due to co-occurring chronic medical conditions among stroke survivors.